Upaya Meningkatkan Perilaku Toleransi pada Anak Usia 5-6 Tahun melalui Film Animasi di RA Kartini Sei Rampah - Yani, Rahma; Khadijah, Khadijah; Daulay, Sholihatul Hamidah (Darul Yasin Al Sys, 2024)
This study aims to determine the improvement of tolerance behavior through animated films at RA Kartini Sei Rampah, addressing various problems and solutions. To collect data, the author used classroom action research methods. The research was conducted in two cycles, each consisting of four stages: planning, action/implementation, observation, and analysis/action. The sample consisted of 20 students. Using animated films as a medium can improve tolerance behavior in children aged 5-6 years at RA Kartini Sei Rampah during the 2023/2024 academic year. This is shown by the results of pre-action observations, which revealed that 2 children, or 25%, were beginning to develop tolerance behavior, while 15 children, or 75%, had not yet developed. In the first cycle, the number increased to 10 children, or 50%, who developed as expected, 8 children, or 40%, who were beginning to develop, and 2 children, or 10%, who had not yet developed. In the second cycle, the results improved further, with 7 children, or 35%, developing very well, 11 children, or 55%, developing as expected, and 2 children, or 10%, who were beginning to develop. The results of this study show that animated films can enhance children's tolerance behavior.